Extracardiac manifestations of connective tissue dysplasia in mitral valve prolapse - A. V. Klemenov (Российский кардиологический журнал)
Mitral valve prolapse (MVP) is the most studied manifestation of connective tissue dysplasia (CTD). Congenital connective tissue defect, lying in the base of the heart anomaly in MVP leads to another internal organs changes. In review the information about extracardial manifestations of CTD concomitant with MVP, such as venous insufficiency, tracheobronchial dyskinesia, gastrointestinal disorders, nephroptosis, genital prolapse, hemostasis pathology is presented.